Stated preferences of adolescents and young adults for sexual and reproductive health services in Africa: a systematic review - Melaku Birhanu Alemu; Richard Norman; Jaya Dantas; Daniel Gashaneh Belay; Tsegaye G. Haile; Gavin Pereira; Gizachew A. Tessema (Sexual and Reproductive Health Matters)
Adolescents and young adults (AYAs) constitute approximately 30% of the African population and face significant challenges in accessing sexual and reproductive health (SRH) services. Low service uptake, despite availability, may indicate service provision misalignment with AYAs' preferences. This reflects the health sector gap and will partly compromise AYAs' rights. This study synthesised stated preference studies on SRH services among AYAs in Africa, following the PRISMA 2020 guidelines. Searches were conducted across six databases (MEDLINE, EMBASE, PsycINFO, CINAHL, Scopus and Global Health) and Google Scholar for grey literature on 24 April 2024. The attributes used to measure SRH preferences were classified based on the Donabedian quality of healthcare framework. A risk of bias assessment was conducted to evaluate the quality of included studies. The review was registered in PROSPERO (CRD42023386944). From 8,329 identified records, 16 studies with 8,005 participants from six countries were included in the final analysis. The attributes used were related to the structural (44.3%), process (41.7%) and outcome-related (13.9%) dimensions. The most important attributes were the cost of services, effectiveness of treatment and treatment frequency. Conversely, the least important attributes were treatment side effects, treatment and medical test sample collection characteristics, provider characteristics (age, gender and profession), and incentive type and recipient. In conclusion, AYAs’ preferences were mainly influenced by cost, treatment effectiveness and incentive distribution methods. Policymakers need to develop affordable and effective SRH programmes with tailored incentives to align with AYAs’ preferences to improve service uptake. However, these insights reflect data from a limited range of African countries.